IMPROVING STUDENT’S VOCABULARY SKILL BY USING ANIMATION FILM ON ENGLISH LESSON IN CLASS V PRIMARY SCHOOL MEDAN ESTATE - Eva Betty Simanjuntak; Rara Sintia Lubis (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: The problem in this study is the low ability of vocabulary students in English subject matter of vocabulary mastery. The purpose of this study is to improve students' vocabulary skills in understanding English vocabulary by using animation film. This research used PTK design. The Subjecs in this study students class VA SD Negeri 106162 Medan Estate School Year 2016/2017 about 1 class of 34 students which consists of 17 male students and 17 female students. Implementation of the action is done for 2 cycles, where each cycle is done two meetings. In 2 cycles there are 4 meetings. In each cycle is done 4 stages of Planning, Action, Observation and Reflection. Instruments that is used in this research is the ability of vocabulary testand observation sheets.Keywords: media, animation film, english, vocabulary ability Abstrak: Masalah pada penelitian ini adalah rendahnya kemampuan vocabulary siswa pada mata pelajaran bahasa Inggris materi penguasaan kosakata. Tujuan penelitian ini adalah untuk meningkatkan kemampuan vocabulary siswa pada materi memahami kosakata bahasa Inggris dengan menggunakan media film animasi.Penelitian ini menggunakan desain PTK. Subjek dalam penelitian ini siswa kelas VA SD Negeri 106162 Medan Estate Tahun Ajaran 2016/2017 sebanyak 1 kelas yaitu 34 siswa yang terdiri dari 17 siswa laki-laki dan 17 siswa perempuan. Pelaksanaan tindakan dilakukan selama 2 siklus, dimana setiap siklus dilakukan dua kali pertemuan. Dalam 2 siklus ada 4 kali pertemuan.Dalam setiap siklus dilakukan 4 tahap yaitu Perencanaan, Tindakan, Observasi dan Refleksi.Instrumen yang digunakan dalam penelitian ini yaitu tes kemampuan vocabulary dan lembar observasi.Kata Kunci: media, film animasi, bahasa Inggris, kemampuan vocabulary